The Effect of Relative Standing on Considerations About Self-Employment - Stefan Schneck (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
This paper uses unique German data to examine the effects of the relative standing on the individual propensity to become self-employed in the next two years. The results suggest that the relationship between relative wage positions and propensity to become self-employed is U-shaped. This is interpreted as evidence that low status translates into entrepreneurial motivation for workers in low relative wage positions. Employees with high relative standing, in turn, seem to be more concerned about the lack of future career prospects in paid employment and consider self-employment as a next step on the individual career ladder.
Keywords: L26; L29; 330; Relative wage position; status; self-employment